Developing a critically reflexive practice for art therapists using external perceptions of art therapy. Issue 2 (3rd March 2016) - Van Lith, Theresa; Voronin, Lorelei
Abstract: This critical inquiry explored external perceptions of art therapy. By focusing on the organizational contexts and structures that art therapy practices are typically situated within, the purpose of the study was to understand: How the values that art therapists intrinsically hold within practice transmitted, translated, and interpreted by other mental health professionals. To gain rich and detailed views, nine mental health professionals were interviewed. Through analysis of the findings, a critically reflexive form of practice was developed to assist art therapists in substantiating their role, while strengthening a team mentality to provide better services to their clients. Study implications involve the need to further explore how art therapists can develop professionally, as well as expand on strategies for how art therapy can be further valued within mental health systems.